Prospek Ekonomi Syariah dalam Menjawab Tantangan Keadilan Sosial dan Kapitalisme Global - Muhammad Yazi (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2009)
In Islamic perspective, money is merely a means of economic transaction.Â It is not a commodity, but a means to achieve added value. Such a concept is contradictory to the interest-based banking system in which money â€œmakesâ€ money regardless its productivity. To gain profit money should be employed in basic economic activity, be it is directly channeled such as trading, leasing and so forth, or indirectly conducted through capital partnership to carry out an aspect or several aspects of an economic activity. One crucial solution that the government must consider in recovering Indonesian economy is the implementation of shariâ€™ah economy. Shariâ€™ah economy has strong commitment in poverty alleviation, law enforcement, economic growth, interest abolition, and the prohibition of currency speculation to create economic stability. Shari;ah economy which is founded upon justice shows excellent concept in facing monetary upheavals compared to interest-based system. It is a fact that global economists agree on. In the future, government must pay more attention to Islamic economy system which has been proven resistant in crisis time.Â Â Islamic economy system, which is represented by shariâ€™ah financial institution have shown its vigor and survided because of its profit sharing principle so that it did not undergo negative spread as those interest-based banks did. In fact, the Islamic banking immensely grows in those rainy days whereas some interest-based banks surged down and collapsed and some other banks were recapped by the government with 650 zillion rupiahs. Every year, Indonesian national budget is drained to pay that recap obligation interest which it should be allocated to poverty alleviation programs. It is the cost that we have to pay if we keep hanging on capitalistic economy which revolves around interest.